Medical students’ reflective capacity and its role in their critical thinking disposition - Zohreh Khoshgoftar; Maasoumeh Barkhordari-Sharifabad (BMC Medical Education, 2023)
Abstract Background Developing reflective capacity and critical thinking is one of the prerequisites of education in health professions, especially medicine. This study aimed to determine the reflective capacity of medical students and its role in their critical thinking disposition. Methods In this cross-sectional descriptive research, conducted in 2022, a total of 240 medical intern students were selected using the convenient sampling method. Data were collected using a reflective capacity questionnaire and critical thinking disposition questionnaire and analyzed with descriptive and inferential statistics using SPSS20. Results The mean reflective capacity was 4.53 ± 0.50, and mean critical thinking disposition was 127.52 ± 10.85. Among the dimensions of reflection, “active self-appraisal (SA)” and “reflective with others (RO)” had the highest and lowest means, respectively. The dimensions of critical thinking disposition with the highest and lowest means were related to innovation and intellectual maturity, respectively. Reflective capacity and its dimensions were found to have a direct and statistically significant relationship with critical thinking disposition and its dimensions. Regression analysis results showed that reflective capacity accounts for 28% of students’ critical thinking disposition. Conclusion The relationship between students’ reflective capacity and their critical thinking disposition has rendered reflection as one of the necessary components of medical education. Thus, determining the learning activities by considering the reflection process and models will be very effective in creating and strengthening critical thinking disposition.